2023
DOI: 10.1111/1753-0407.13368
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes management: Room for improvement

Abstract: Aims/Hypothesis Optimal diabetes care and risk factor management are important to delay micro‐ and macrovascular complications in individuals with type 1 diabetes (T1D). Ongoing improvement of management strategies requires the evaluation of target achievement and identification of risk factors in individuals who do (or do not) achieve these targets. Methods Cross‐sectional data were collected from adults with T1D visiting six diabetes centers in the Netherlands in 2018. Targets were defined as glycated hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 3 Moreover, children with T1D are prone to suffering from life-threatening complications due to poor metabolic control. 4 Therefore, it is imperative to discover biomarkers that can identify early-stage disease in most, if not all, individuals, in order to delay β-cell loss and improve prognostic outcomes. Although islet-specific autoantibodies have proven valuable in predicting future T1D onset, it should be noted that not all autoantibody-positive individuals progress to clinical T1D.…”
Section: Main Textmentioning
confidence: 99%
“… 3 Moreover, children with T1D are prone to suffering from life-threatening complications due to poor metabolic control. 4 Therefore, it is imperative to discover biomarkers that can identify early-stage disease in most, if not all, individuals, in order to delay β-cell loss and improve prognostic outcomes. Although islet-specific autoantibodies have proven valuable in predicting future T1D onset, it should be noted that not all autoantibody-positive individuals progress to clinical T1D.…”
Section: Main Textmentioning
confidence: 99%
“…Several reports have clearly showed that commercially available AID systems facilitate PwT1D to reach these glycaemic goals by adjusting in real‐time basal insulin and delivering autocorrection boluses, as reviewed recently 6,7 . Altogether, these improvements in glucose control provide important conditions to minimize the daily burden of this chronic disease and to prevent diabetic complications 8 . However, it has been underlined that some participants were still unable to reach these glucose targets, largely because by the necessity to inform the system on levels of carbohydrate (CHO) consumption before meals and on expected changes in physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Altogether, these improvements in glucose control provide important conditions to minimize the daily burden of this chronic disease and to prevent diabetic complications. 8 However, it has been underlined that some participants were still unable to reach these glucose targets, largely because by the necessity to inform the system on levels of carbohydrate (CHO) consumption before meals and on expected changes in physical activity. This confirms that individual and psychosocial factors are important parameters for optimal diabetes management and sustained use of AID systems.…”
Section: Introductionmentioning
confidence: 99%